Exploring Career Maturity: A Comparison of Student-Athletes and Non-Athletes at a Division I Institution - Walter Tarver, III (Journal of Applied Sports Management, 2020)
This quantitative study compared the career maturity of student-athletes and non-athletes at a Division I university, and assessed career maturity differences among student-athletes. Super’s Theory of Career Development served as the theoretical framework, while the Career Maturity Inventory-Revised Attitude Scale (CMI-R/AS) was utilized to collect data. Student-athletes were found to exhibit lower levels of career maturity than non-athletes. Among student-athletes, males scored lower on career maturity than females. Additionally, those identifying more closely with their athletic identities, those with higher aspirations to play professional sports, those with stronger beliefs in the likelihood that they would play professional sports, and those competing in revenue sports (football and men’s basketball) had lower levels of career maturity. Finally, as year of athletic eligibility increased, student-athletes’ career maturity increased.
Keywords: Intercollegiate Athletics; Management; NCAA; Student-Athletes